PENGETAHUAN, SIKAP, DAN PERILAKU MAHASISWA KEPERAWATAN DI KOTA MALANG TERHADAP PENCEGAHAN HIV-AIDS - Ikoh Rofikoh; Faqih Ruhyanudin; Edi Purwanto; Anis Ika Nur Rohmah; Titik Agustiyaningsing; Hanik Tri Rahayu; Chairul Huda Al Husna (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2023)
Deviant behavior among students such as having sexual relations outside of marriage, drinking alcohol and even using narcotics increases the risk of transmitting HIV-AIDS. Good behavior can prevent the occurrence of HIV-AIDS. The purpose of this study was to determine the knowledge, attitudes, and behavior of nursing students in preventing the transmission of HIV-AIDS. This research is quantitative descriptive research with a survey approach. The population is nursing students in Malang City with a total of 88 respondents selected by accidental sampling. The research instrument used the AIDS Prevention Questionnaire/ Cuestionario para la Prevención del Sida (CPS) questionnaire-a valid and reliable AIDS prevention questionnaire. Data collection was carried out online using the Google form from December 2022 - January 2023. Data analysis used descriptive analysis. The results showed that 80.7% of students had good knowledge of HIV-AIDS, and 19.7% of other students had sufficient knowledge. Most of the students (72.7%) had a good attitude category, 14.8% of students were quite good, and 12.5% of students were not good enough. As many as 78.3% of students have good preventive behavior, 8.0% of students are quite good, and 14.8% of students have poor preventive behavior. The majority of nursing students in Malang have good knowledge, attitudes, and behavior toward the prevention of HIV-AIDS transmission, but there are still moderate or poor categories that require more attention from the campus.